Electroplating of copper metallization of sub-micron integrated circuits - Law, Shao Beng. (2008)
In this project, plating in electrolytes with and without additives was evaluated. The impact of these electrolytes and various plating parameters such as current density, current pulse waveforms, wafer rotation on the characteristics of the plated Cu film were studied.